High-conductivity silicon based spectrally selective plasmonic surfaces for sensing in the infrared region. (30th December 2016) - Gorgulu, K; Gok, A; Yilmaz, M; Topalli, K; Okyay, A K
Abstract: Plasmonic perfect absorbers have found a wide range of applications in imaging, sensing, and light harvesting and emitting devices. Traditionally, metals are used to implement plasmonic structures. For sensing applications, it is desirable to integrate nanophotonic active surfaces with biasing and amplification circuitry to achieve monolithic low cost solutions. Commonly used plasmonic metals such as Au and Ag are not compatible with standard silicon complementary metal–oxide–semiconductor (CMOS) technology. Here we demonstrate plasmonic perfect absorbers based on high conductivity silicon. Standard optical lithography and reactive ion etching techniques were used for the patterning of the samples. We present computational and experimental results of surface plasmon resonances excited on a silicon surface at normal and oblique incidences. We experimentally demonstrate our absorbers as ultra-low cost, CMOS-compatible and efficient refractive index sensing surfaces. The experimental results reveal that the structure exhibits a sensitivity of around 11 000 nm/RIU and a figure of merit of up to 2.5. We also show that the sensing performance of the structure can be improved by increasing doping density.